Facebook recruitment and online interviewing - suitable for qualitative research in migration? - Dominika Pszczółkowska (University of Warsaw, Centre of Migration Research (CMR), 2020)
Facebook is increasingly used for recruiting research participants, especially for quantitative studies and in research in the field of health. Migration scholars have also noticed its potential. This article aims to discuss the use of the online social network for recruiting respondents for qualitative interviews with migrants. It is based on a review of the literature and a recently completed research project with 73 Polish migrants to four other countries of the European Union: the UK, Germany, Ireland and the Netherlands. The use of Facebook for recruitment brought huge benefits: it allowed for access to a wide range of respondents, both in terms of geographic location and access to people who would not have agreed to an interview in person. Challenges concerned the representativeness of members of Polish Facebook groups, technical issues, and threats to the privacy of the respondents. The article also discusses the benefits and difficulties linked with conducting interviews online through communicators such as Skype or Facebook Messenger.
Keywords: 330; Facebook recruitment; migrants; online interviews; Skype; qualitative research